Does Innovation Mediate Family Support for Business Performance? - Ida Puspitowati; Yusi Yusianto (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
Business performance remains a concern in business, as well as for SMEs. This study aims to investigate whether product innovation can be a mediator of the influence of family support on SME performance, because innovation is one of the important things for an entrepreneur. This study used a quantitative approach with a cross-section method, with purposive sampling of food and beverage SMEs in Jakarta. Data collection through Google Form obtained 50 questionnaires that were completely filled out and met the requirements. The analysis in this study with Partial Least Square-Structural Equation Modeling (PLS-SEM), and SmartPLS v.4.0 was used in data processing. After the variables were declared valid and reliable, testing was carried out on the four hypotheses proposed. From the test results, the path coefficient results of the family support variable have a positive but insignificant effect on the performance of food and beverage SMEs in Jakarta. Product innovation has a positive and significant effect, and product innovation is able to mediate the influence of family support on SME performance. The results of this study are expected to be input for policy makers for SMEs to be able to improve performance through product innovation, so that through product innovation, SMEs are able to compete and experience improvements in performance.